Mapping of vulnerability to rangeland degradation using AHP-GIS & RPAS in the Pomacochas micro-watershed -Peru - Silva-López, Jhonsy O. (2023)
In Peru,rangeland monitoring is increasingly essential to support farmers and strengthen new public policies for sustainable management at the watershed level. In this research, we sought to map the vulnerability to grassland degradation in the Pomacochas micro-watershed, Amazonas -Peru. For this, criteria were used (NDVI, precipitation, SOM, soil texture, soil pH and slope). Also, based on expert consultation and the Analytical Hierarchy Process (AHP), the importance of the criteria was weighed. Then, the land suitability map was generated to assess rangeland vulnerability by weighted superimposition of the criteria maps. NDVI was the most important criterion, while land slope was the least important. AHP and GIS based modeling shows that about 4012.08 km2(62.98%) of the total study area is in the category "slightly vulnerable" (C3) to grassland degradation. The results were also validated by means of four validation plots using images from a Remotely Piloted Aircraft (RPA). The study will provide support for decision making in the management of grasslands in micro-watersheds